Portal cibernautas: produção de textos multimodais a partir do gênero infográfico digital - Almeida, Elizabeth Mota Nazareth de (2018)
With the advent of the internet, the hypermedia and multimodal reading/writing are increasingly present in our daily lives. This is a challenge to our pedagogical practice in conducting the experiment student readers and writers, from that digital technology context. These opportunize shares the development of autonomous and critics individuals adequate to the concerns and demands of the society in which they are inserted. In this context, we have developed this research with the goal of promoting didactic-pedagogic actions focused on collaborative writing of infographics, combining the use of the DICT to teaching-learning in Portuguese Language, with a view to enlargement skills student writers of the Tempo Juvenil 04, in the night shift of a school in Feira de Santana, Bahia. Based on the propositions of qualitative research, this intervention research is inserted in the nature applied research through collaborative technical procedure, where we develop didactic sequences focused on practices of reading and writing of multi-modal texts, from the genre infographic, with the support of an online platform, entitled Portal Cibernautas, and a schedule of Activities designed by the teacher-researcher. These actions were based on a multidisciplinary theoretical contribution composed mainly by Kleiman (1995; 2005), Goulart (2006) and Tfouni (2010) introducing the concepts of literacy, in Rojo (2009; 2012) that introduces the proposal of pedagogy of multiliteracy; in Lévy (1999), Xavier (2007; 2011), Tapscott (2010) and Dionísio (2006), which helped us in understanding the virtual universe, its features and multiple tools; in addition to Mary Kato (1987); Koch and Elias (2010) and Portela (2012) on issues concerning cognitive processes of reading and writing. We use still Dolz; Noverraz; Schneuwly (2004), Costa-Hübes (2009) and Barreiros; Souza (2015) to base the proposal for didactic teaching of the genres and didactic sequences. More specifically in the case of the textual genre, infographic, we are based on Coscarelli (2016), Ribeiro (2016) and Teixeira (2010). Based on these theorists, we develop intervention actions to the new needs of the students, providing theirs expansion of the writing competence. Therefore, bearing in mind that the competence development processes are large, writer, in this research, embrace some aspects of writing and realize, from data observed in this study, to conduct the student to readers and writers practices multimodal text, as the infographic, we contribute to the broadening of skills focused on search and selection of data and information in accordance with its goals of reading and writing, composition of sense to correlate texts verbal and non-verbal, text rewrite the original idea through the use of paraphrase, writing informative texts, production of hipermidiáticos texts that feature themes of social relevance. In addition, the expansion of autonomy, collaboration, creativity and criticality of the subject facing the wishes and requirements of a technological society. After the application of the proposed intervention, the results shown that the practices of reading/writing of the multimodal and hypermedia texts in Portuguese Language classroom, together with DICT, bring to supportive role in the process of construction and expansion of knowledge geared to writing abilities.